Research on Carbon Emission of Steel Structure During Production Process - Wang, Ziyan (Transactions on Engineering and Technology Research, 2024)
In recent years, there has been increasing global concern about climate change and sustainable development. At the same time, there is a growing awareness of environmental responsibility in civil and construction projects. In this paper, two different types of steel materials are discussed. Then, comprehensive assessments of the environmental impact of their production processes have been carried out, with special emphasis on carbon emissions. These analyses highlight the ecological impacts associated with each material type, which also facilitates subsequent comparative assessments aimed at identifying potential ways to reduce environmental impacts. The investigation shows that there is a significant negative correlation between the tensile strength of steel and the volume of the material used, which in turn leads to a proportional reduction in carbon emissions. The research results can show the environmental benefits of improving the compositional integrity of steel. This paper hopes to make some theoretical contributions to the global mission of reducing carbon emissions.